PERENCANAAN PENGGUNAAN LAHAN KOMODITAS UNGGULAN PERKEBUNAN DI KABUPATEN TANAH DATAR - Astriana Rahmi Setiawati; Santun R.P Sitorus; Widiatmaka Widiatmaka (TATALOKA, 2016)
Tanah Datar is one of regency in West Sumatera that has a great potential in agriculture, which is more than 70% of  its population are farmers. Unfortunately, the economic income of this regency is lowest than another regency in West Sumatera. This research aimed: (1) to identify superior estate comodities of Tanah Datar Regency; (2) to identify present land use of Tanah Datar Regency; (3) to analyze land availability and to evaluate land suitability of superior estate commodities; (4) to arrange the direction of superior estate commodities development. Land  suitability  evaluation was  done  by  using the matching method  between land characteristics and crops requirement. The study showed that the available land for development of  superior comodities is about 38.210 ha which is suitable for robusta coffee (X koto); nutmeg (Batipuh); cocoa (Batipuh selatan, Rambatan, Limo kaum, Tanjung emas, and Lintau buo utara); rubber (Padang gantiang); cassievera (Pariangan and Salimpauang); vanilla (Sungai tarap); and arabica coffee (Salimpauang), respectively.